Design, Synthesis, In Silico Studies and In Vitro Evaluation of New Indole- and/or Donepezil-like Hybrids as Multitarget-Directed Agents for Alzheimer's Disease - Violina T. Angelova; Borislav Georgiev; Tania Pencheva; Ilza Pajeva; Miroslav Rangelov; Nadezhda Todorova; Dimitrina Zheleva-Dimitrova; Elena Kalcheva-Yovkova; Iva V. Valkova; Nikolay Vassilev; Rositsa Mihaylova; Denitsa Stefanova; et al. (MDPI AG, 2023)
Alzheimer's disease (AD) is considered a complex neurodegenerative condition which warrants the development of multitargeted drugs to tackle the key pathogenetic mechanisms of the disease. In this study, two novel series of melatonin- and donepezil-based hybrid molecules with hydrazone (3a-r) or sulfonyl hydrazone (5a-l) fragments were designed, synthesized, and evaluated as multifunctional ligands against AD-related neurodegenerative mechanisms. Two lead compounds (3c and 3d) exhibited a well-balanced multifunctional profile, demonstrating intriguing acetylcholinesterase (AChE) inhibition, promising antioxidant activity assessed by DPPH, ABTS, and FRAP methods, as well as the inhibition of lipid peroxidation in the linoleic acid system. Compound 3n, possessing two indole scaffolds, showed the highest activity against butyrylcholinesterase (BChE) and a high selectivity index (SI = 47.34), as well as a pronounced protective effect in H2O2-induced oxidative stress in SH-SY5Y cells. Moreover, compounds 3c, 3d, and 3n showed low neurotoxicity against malignant neuroblastoma cell lines of human (SH-SY5Y) and murine (Neuro-2a) origin, as well as normal murine fibroblast cells (CCL-1) that indicate the in vitro biocompatibility of the experimental compounds. Furthermore, compounds 3c, 3d, and 3n were capable of penetrating the blood-brain barrier (BBB) in the experimental PAMPA-BBB study. The molecular docking showed that compound 3c could act as a ligand to both MT1 and MT2 receptors, as well as to AchE and BchE enzymes. Taken together, those results outline compounds 3c, 3d, and 3n as promising prototypes in the search of innovative compounds for the treatment of AD-associated neurodegeneration with oxidative stress. This study demonstrates that hydrazone derivatives with melatonin and donepezil are appropriate for further development of new AChE/BChE inhibitory agents.